Implementasi Sustainability Development Goals Melalui Program Integrated Sustainability Indonesia Movement (I-SIM) for Cities 2022 oleh PT Surveyor Indonesia - Sofwan, Nabila Martagati; Subekti, Priyo (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
PT Surveyor Indonesia is a survey, inspection, consultancy and certification services company. As an agent of development for the Government, PT Surveyor Indonesia pays special attention to the global issue of Sustainability, which in collaboration with APEKSI (Association of City Governments throughout Indonesia) has developed the Integrated Sustainability Indonesia Movement (I-SIM) for Cities programme, which aims to fully support the acceleration of the City's SDGs achievement and encourage the development of city government capabilities towards international sustainable city standards. The I-SIM for Cities programme is part of the SDGs Annual Conference 2022 organised by the Ministry of National Development Planning/Bappenas. With the spirit of inclusivity or no one left behind, I-SIM for Cities creates a multi-stakeholder penta helix engagement, such as government, academia, philanthropy, community, business, and media. This research aims to find out how the implementation of SDGs carried out by PT Surveyor Indonesia through the I-SIM for Cities programme. The method used in this research is descriptive-qualitative method. The results of this study indicate that out of 98 cities in Indonesia, 74 cities are registered in I-SIM for Cities. Then, of the 74 cities will be re-selected into 15 cities that will enter the judging process. Then selected again to 6 cities to enter the awarding stage. This is seen based on the percentage of data filling, data quality, and the availability of superior programmes.